Plant diversity in the homegardens of Karwar, Karnataka, India - SHIVANAND BHAT1; M. JAYAKARA BHANDARY; L. RAJANNA (Society for Indonesian Biodiversity, 2014)
Bhat S, Bhandary MJ, Rajanna L. 2014. Plant diversity in the homegardens of Karwar, Karnataka, India. Biodiversitas 15: 229-235. A study was conducted in 50 selected home gardens of Karwar, Karnataka, India to document their floristic diversity and composition withregard to life forms and uses. As many as 210 species of flowering plants belonging to 69 families were recorded. Euphorbiaceae(13species), Apocynaceae (11spp.), Cucurbitaceae (10 spp.) and Fabaceae (10 spp.) are the predominant families. Shrubs are thedominant life forms (73 spp.) followed by trees (61 spp.), herbs (42 spp.) and climbers (24 spp.). Areca palm (Areca catechu), coconutpalm (Cocos nucifera), mango tree (Mangifera indica), banana (Musa paradisiaca), shoe flower (Hibiscus rosa-sinensis) and holy basil(Ocimum tenuiflorum) are the most common plants occurring in all of the 50 studied gardens. 38% of the plant species are grown mainlyfor ornamental and aesthetic purposes while 33% of the species are used for obtaining food products like fruits and vegetables and 22%of the plants are mainly used for medicinal purposes. The predominance of ornamental species makes the home gardens of Karwardifferent from those occurring in other regions in which mostly food plants form the major component.